Challenges of 'VoiP' Communication Systems for Air Traffic Management - Miroslav Borković; Petar Obradović; Igor Franolić (Promet - Traffic&Transportation, 1970)
Today's dense air traffic and the worldwide move to FutureAir Navigation System (FANS) concepts demand a high levelof modem and reliable Air Traffic Control (ATC) equipmentto accommodate customer requirements now and in the future.The work tries to answer the questions that indicate the fact whya new VCS generation (Voice Communication System) basedon VoiP (Voice over Internet Protocol) has some essentialcomparative advantages related to the conventional VCS. Oneof the key arguments featuring the VoiP technology is its lowprice a~d wide application in modem communications. Becauseof the fact of the PC-based HMI (Human Machine Interface)application, IP-VCS could easily be implemented in thenew A TM data network infrastructure. In the future, the VoiPtechnology development and VoiP VCS will have to prove thatthey are ready to meet the requirements of more flexible, saferand cheaper way of air traffic management.